FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS MANAGEMENT PADA PERUSAHAAN MANUFAKTUR DI BEI - Liana Sulasti Hasan, Lukman Surjadi (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study is to find out whether the factors of profitability, leverage, firm size, and growth affect earnings management in manufactur companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling method used is purposive sampling with total sample 43 data. Data processing is done by using E-views 9.0. The results showed that profitability has a positive effect on earnings management, while leverage and growth do not have positive effect on earnings management, and firm size do not have negative effect on earnings management.